An empirical analysis of COVID-19 response: comparison of US with the G7. Issue 6 (2nd November 2021) - Barari, Mahua; Kundu, Srikanta; Mitra, Saibal
ABSTRACT: We compare the US policy response to COVID-19 with its G7 counterparts between March and September 2020. The G7 countries, while economically and ideologically aligned, have instituted vastly different policies to mitigate the spread of the disease with varying degrees of compliance. To quantify the effect of policy responses on the spread of infections, we estimate beta for each country which is the slope coefficient of daily new cases in each country regressed against world new cases. First, we test for structural breaks in daily data for world new cases using the Bai Perron method which endogenously determines break points. We obtain five break dates that allow us to divide the time period into six windows and estimate betas separately for each window. Next, we rank the G7 countries based on their beta values for each window. Our empirical findings suggest that countries that eased their lockdown measures moderately while enforcing nationwide mask mandate and comprehensive contact tracing generally performed better in mitigating the spread of new infections. Furthermore, countries with higher degree of compliance saw improvement in their rankings. US was ranked mostly in the bottom half of the G7 group but not always the worst.